2009
DOI: 10.1002/cbic.200900176
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide‐Hydrolase‐Initiated Hydrolysis/Rearrangement Cascade of a Methylene‐Interrupted Bis‐Epoxide Yields Chiral THF Moieties without Involvement of a “Cyclase”

Abstract: In contrast with electrophilic enzyme-catalysed cyclisations in terpenoid biosynthesis, cyclisations of tetrahydrofuran moieties found in several groups of natural products, such as annonaceous acetogenins, neurofurans and phytooxylipins, appear to proceed through a nucleophilic cascade mechanism starting from bis-epoxy fatty acid precursors. This hypothesis was verified by epoxide-hydrolase-catalysed hydrolytic ring-opening/cyclisation cascades starting from a methylene-interrupted meso-bis-epoxide model subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…This fact, together with the low enantioselectivity shown in the kinetic resolution of typical EH substrates, for example, styrene oxide, has partly limited the interest toward its synthetic exploitation. Only a few examples of practical applications of Re ‐LEH in synthetic organic chemistry have been reported to date . In contrast, Re ‐LEH has been recently the subject of different protein engineering studies aimed at the improvement of useful applicative features, such as the stereoselectivity and thermostability …”
Section: Introductionmentioning
confidence: 99%
“…This fact, together with the low enantioselectivity shown in the kinetic resolution of typical EH substrates, for example, styrene oxide, has partly limited the interest toward its synthetic exploitation. Only a few examples of practical applications of Re ‐LEH in synthetic organic chemistry have been reported to date . In contrast, Re ‐LEH has been recently the subject of different protein engineering studies aimed at the improvement of useful applicative features, such as the stereoselectivity and thermostability …”
Section: Introductionmentioning
confidence: 99%
“…Under enzymatic catalysis conditions, the epoxide opening cascade can also be triggered by epoxide hydrolases, followed by a spontaneous cyclization without any cyclase, as described by Faber and co-workers in the desymmetrization of meso bisepoxides. 16 Finally, Hu et al recently revealed that the cascade epoxide opening could also be triggered by the intramolecular attack of a hydroperoxide under basic conditions. 17…”
Section: Thf Synthesis By C-o Bond Formation 1 Epoxide Openingmentioning
confidence: 99%
“…Expansion of this study showed that four different THF-derivatives (representative 82 , 84 ) each with excellent ee and de values were achieved by using EHs from multiple organisms (e.g., Rhodococcus species, Solanum tuberosum , Aspergillus niger , Mycobacterium tuberculosis ). The stereospecificities of the enzymes thereby determined the final stereoselectivities of the products while the cyclization reaction follows Baldwin’s rule without the operation of a cyclase [208].…”
Section: Hydrolase Activity In Rhodococcusmentioning
confidence: 99%